Educational Component as The Most Important Trend in High School Medical Pedagogy - Don A.N (Euro Asian Journal Publishing, 2023)
The article presents the results of a study of the educational component in medical pedagogy of higher education. Education is considered an integral part of the educational process. This is the right trend, since it is important not only for students to acquire professional competencies and knowledge, but also the ability to be specialists with deep cultural properties, including ethical and deontological aspects of the medical profession. The psychological readiness of a good specialist for his professional activity is expressed in his ability to conduct a correct conversation and communicate with patients and their relatives. Thus, educational work in universities, aimed at developing a well-founded high selfesteem of future young specialists, will contribute to the development of broad universal, general professional and professional competencies. The educational work constantly carried out by higher school teachers is aimed at preparing precisely such highly erudite doctors
Keywords: education; pedagogy; higher; medicine